A review of the management of positive biochemical screening for phaeochromocytoma and paraganglioma: a salutary tale. Issue 7 (4th February 2015) - Garrahy, A.; Casey, R.; Wall, D.; Bell, M.; O'Shea, P. M.
Summary Background Phaeochromocytomas (PC) and paragangliomas (PGL) are rare neuroendocrine tumours of chromaffin cells. Diagnosis depends on biochemical evidence of excessive production of catecholamines. This is straightforward when test results are orders of magnitude above the concentrations expected in healthy individuals and those with essential hypertension. Equivocal results pose a management dilemma. Aim We reviewed biochemical screens that were positive and the ensuing management for PC/PGL at our institution. The objective was to inform the development of a standardised approach to investigation and clinical follow‐up. Method All records of positive biochemical screening for PC/PGL were extracted from the laboratory information system between January 2004 and June 2012. Clinical notes of patients with positive results were reviewed. Results A total of 2749 biochemical screens were performed during the evaluation period. Of these, 106 (3.9%) performed on 82 patients were positive. Chart review determined that 12/82 patients had histologically confirmed PC/PG. Of the 70 patients remaining, the most common indication for biochemical screening was hypertension and the medical subspecialty most frequently requesting the test was Endocrinology. The primary team carried out repeat testing on 35/70 (50%) patients and in 29 results normalised. Notably, 35/70 (50%) patients did not have any follow‐up of positive test results. Conclusion This study highlights the necessity for a standardised diagnostic protocol for PC/PGL. We suggest that appropriate follow‐up of borderline‐elevated results should first include repeat biochemical testing. This should be performed under standardised pre‐analytical conditions and where possible off all potentially interfering medications, measuring plasma free metadrenalines.